Green co-extractant-assisted supercritical CO2 extraction of xanthones from Mangosteen pericarp using tricaprylin and tricaprin mixtures - Liu, Hua; Stanslas, Johnson; Ren, Jiaoyan; Suleiman, Norhidayah; Chong, Gun Hean (Multidisciplinary Digital Publishing Institute, 2025)
Xanthones from mangosteen pericarp (MP) are bioactive compounds with promising pharmaceutical and nutraceutical applications. However, their efficient and selective extraction using environmentally friendly solvents remains a challenge. This study aimed to evaluate tricaprylin (C8) and tricaprin (C10) as novel green co-extractants in supercritical carbon dioxide (scCO2) extraction for the recovery of xanthones from MP, using a mass ratio of C8:C10 = 0.64:0.36, hereafter referred to as C8/C10, and to model extraction kinetics for process design and scale-up. Extraction performance was investigated using different C8/C10–MP mass ratios and scCO2 conditions at temperatures of 60 °C and 70 °C and pressures of 250 bar, 350 bar, and 450 bar. A pseudo-first-order kinetic model was applied to describe the extraction profile, and the kinetic parameters were generalized using second-order polynomial functions of temperature and pressure. The highest xanthone yield (39.93 ± 0.37%) and total xanthone content (51.44 ± 2.22 mg/g) were obtained at a 40% C8/C10–MP ratio under 70 °C and 350 bar, where the C8/C10 mixture outperformed other tested co-extractants in both efficiency and selectivity, particularly for α-mangostin. The extraction profiles were well described by the pseudo-first-order kinetic model, and the generalized model predicted the extraction yield with an uncertainty of 2.3%. C8/C10 is a highly effective and scalable co-extractant for scCO2 extraction of xanthones, offering a foundation for industrial applications in food, nutraceutical, and pharmaceutical sectors.